EVALUATION OF ENGINEERING DESIGN ACTIVITIES IN SCIENCE COURSEBOOKS IN TURKEY - Eskici, Gamze (International Online Journal of Education and Teaching, 2023)
This study aims to evaluate the compatibility of engineering design activities in 5-8 grade science coursebooks with the curriculum and to examine their reflection of design principles. The document analysis method was used in the study. Initially, the 5-8 grade science coursebooks recommended by the Ministry of National Education in 2021-2022 were determined. Then, the engineering design activities in these books and the learning outcomes related to engineering and design skills in the 2018 Science Curriculum were determined. As a data collection tool, an engineering design activity evaluation rubric based on engineering design principles was prepared by reviewing the relevant literature. Based on the prepared rubric, the activities in the science coursebooks recommended by the MoNE in 2020-2021 were examined. At the end of the examination, some learning outcomes had more than one engineering design activity, some learning outcomes did not have design activities, and some learning outcomes had design activities in subjects excluding the learning outcomes. Depending on this, the percentages of the coursebooks reflecting engineering design were determined. It was observed that the percentage of the coursebook with more STEM activities reflecting engineering design principles was low.